Evaluation of Nanomedicine Applications of Silver and Zinc Oxide Nanoparticles Using Water Extract of Fresh Turmeric. (1st February 2023) - Saravanan, K.; Natarajan, B.; Nallamuthu, N.; Sadiq, Muhammad; Ramanujam, Ganesh Munusamy
Abstract : Recently, there has been a lot of research into the green synthesis of metal and metal oxide nanoparticles, particularly from plants. To date, however, there has been no published study detailing the synthesis of Ag and ZnO nanoparticles using fresh turmeric extract. In this experiment, silver and zinc oxide nanoparticles were synthesised with an environmentally friendly capping and reducing agent made from fresh turmeric extracts. The synthesised Ag and ZnO nanoparticles were verified using UV–vis, FT-IR, XRD, TGA, HR-SEM, and HR-TEM. The SEM and XRD showed that the synthesised nanoparticles had a size range of 10–30 nm, a highly crystalline form, and a well-almost spherical shape. Medical applications for the synthesised Ag and ZnO nanoparticles include their antibacterial activity against S. aureus and Klebsiella pneumonia. Scavenging activities varied from 20% to 70% for turmeric, 0% to 20% for ZnO, and 40% to 60% for silver. ZnO was found to be more cytotoxic than Ag against THP-I at the tested concentrations. Overall, the biologically synthesised silver and zinc oxide presented in this study offers a safe alternative to synthetic substances and shows promise as a candidate for antimicrobial, antioxidant, and cytotoxic activity in nanomedicine.